Guided reflection: a framework to facilitate and assess reflective practice within the discipline of physiotherapy. - Donaghy ME; Morss K (Physiotherapy Theory & Practice, 2000)
This paper describes a process of guided reflection that aims to facilitate and structure reflection and provide a framework for the assessment of reflective practice within the discipline of physiotherapy. Arguments are presented for moving away from an approach which encourages reflecting on beliefs, values, and attitudes to an approach that is linked more closely to systematic critical enquiry, problem solving, and clinical reasoning. The importance of linking reflection to higher order cognitive processes, specifically the development of memory schema, 'illness scripts', and clinical knowledge, are stressed. Emphasis is placed on gathering evidence of reflection to allow knowledge that is normally tacit to become more explicit and available for critical appraisal. Therefore, the framework, which is intended to facilitate reflection in clinical practice, asks students to write a personal reflective account, supported by evidence. The framework builds on the thinking and the decision-making process associated with the physiotherapy student's examination of the patient and as such it is embedded within clinical reasoning.